Analysis of Rice Farmers' Decisions in Selling Production Results in East OKU Regency - Slamet; Munajat, Munajat; Oktarina, Yetti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Grain is rice fruit that has been threshed from panicles (straw). Grain is a commodity resulting from rice production which is a staple food in Indonesia. This research will be carried out in East OKU Regency, specifically in East Buay Madang, Buay Madang and Madang Suku I Districts. The location determination was carried out purposively. The research method used in this research is the case study method. According to Sriati (2014), the case study method (case study) The sampling method used in the research entitled analysis of rice farmers' decisions in selling their production in East OKU Regency is multi-stick random sampling. Respondents were taken from three sub-districts, namely East Buay Madang, Buay Madang and Madang Suku I, with the reason that these three sub-districts constituted 118 respondents. The results of the research show that the factors that influence farmers' decisions in selling rice production in East OKU are independent variables, namely production, urgent needs, middlemen and milling costs which significantly influence farmers' decisions. Meanwhile, the labor variable does not have a significant effect on farmers' decisions. Keywords: Grain, Rice, Decree